(untitled) (Bangladesh Critical Care Journal, 2017)
Gastrointestinal infestation with Ascaris lumbricoides is common in the tropical countries. A wide range of clinical presentations are reported for gastrintestinal ascariasis in both adults and children. We report a case of diarrhea causing malnutrition in ICU due to Ascaris infestation. Bangladesh Crit Care J March 2017; 5(1): 70-71